Systematic Review on The Factors That Influence Well-Being Among Teachers (Sains Humanika, 2021)
Increasing the well-being of teachers in schools is an important issue that needs to be discussed. Nowadays, there are many problems related to the teacher, which will affect the teacher's professionalism in teaching. This systematic review aims to synthesize factors that can impact teacher welfare. The journal search database includes EBSCOHOST, PROQUEST, EmeraldInsight, and ScienceDirect, published in the last ten years (2010-2019). The keywords used are "Welfare" OR "Psychological Welfare" OR "Subjective Welfare" OR "Subjective Welfare" AND Teacher. Article selection uses PICOSS (Population, Intervention, Comparator, Result Variable, Study Design, and Setting). There are three syntheses of predictors of teacher well-being variables, namely personal factors, professional factors, and organizational factors.
Keywords: Personal Factors; Professional Factors; Organizational Factors; Well-Being; Teacher